Life Cycle Assessment of Organic Waste Treatment by Composting and Anaerobic Digestion for the City of Cuenca – Ecuador - Cobo, Juan Carlos; Tallada Cebrián, Adria (My University, 2025)
This thesis explores the environmental performance of anaerobic digestion (AD) and composting as waste management solutions for the organic fraction of municipal solid waste (OFMSW) in Cuenca, Ecuador. Using Life Cycle Assessment (LCA) methodologies, it evaluates key environmental impacts such as global warming potential and photochemical oxidant formation, aiming to identify the most suitable method for reducing the amount of organic waste sent to landfills. The results indicate that anaerobic digestion has strong potential to reduce greenhouse gas emissions, particularly when biogas is effectively captured and used. On the other hand, composting, while less effective in terms of emission reductions, is more cost-efficient and can play a valuable role in improving soil health. Despite these benefits, both technologies face considerable challenges in the Latin American and Caribbean (LAC) region, where the focus is often still on meeting basic waste management needs, such as establishing sanitary landfills. The high costs and limited development of AD in the region also raise concerns about its viability. The study highlights the importance of understanding the composition of OFMSW, as this has a direct impact on the efficiency of AD systems. Future research should explore the potential of co-digesting OFMSW with other types of organic waste to boost biogas production. Additionally, factoring in socio-economic aspects—such as the costs of implementation, potential economic gains from energy generation, and effects on local communities—will provide a fuller picture of the sustainability and practicality of these technologies. Ultimately, the findings suggest that while both AD and composting offer clear environmental benefits, their adoption must be guided by local priorities and infrastructure readiness. Addressing these regional factors is crucial for optimizing resource recovery and minimizing environmental impacts.
Keywords: Anaerobic digestion; Composting; Life Cycle Assessment (LCA); Organic fraction of municipal solid waste (OFMSW); Greenhouse gas emissions; Biogas; Waste management; Ecuador; Latin America and Caribbean (LAC) region; Socio-economic considerations; Environmental sustainability; Resource Recovery